Thésaurus et interopérabilité des données archéologiques : le projet HyperThesau - Emmanuelle Perrin (Humanités Numériques)
The HyperThesau project (IMU Labex, University of Lyon) aims at building archaeological data interoperability through a standardised, shared vocabulary. As proof of concept, it initiates a pivot thesaurus, which maps the concepts of archeology on to international knowledge organisation systems, using semantic Web technologies. This thesaurus should be used for data processing, recording, crawling and retrieval within a vast digital ecosystem: metadata, databases, library catalogs, digital libraries and platforms.The computer and documentary processing of archaeological data implies that language itself becomes a study topic. The method used to build this thesaurus consisted in collecting, processing and structuring archaeological vocabulary by trying to determine the underlying meaning of the terms and building bridges between the classifications used by archaeologists and current knowledge organisation systems. A thesaurus can be a tool for reconciling research and information science. It also feeds methodological reflections, opening interesting historiographical perspectives.